Visual art as an instrument of reorganization of post-catastrophic memory - O. O. Geraschenko, (Ukrainian Cultural Studies, 2019)
This article provides analysis of the Art approach towards transformation of longstanding traumatic experience in different countries, suggests possible consequences for the society in case if the catastrophic memory remains un-reorganized and grounds conclusion as for need to review approaches towards the later problem in Ukraine.During last three decades of statehood one can observe dynamic movement of Ukraine toward cultural assertion. One of its important elements is the comprehension of public traumatic experience. The latter bares immense importance for the success of Ukraine as a state due to the fact that for generations Ukrainians have been accumulating memory of mournful events that took place in the lives of their ancestors without the possibility to carry out the proper work of sorrow.Topicality of the mentioned problem has a special meaning nowadays considering that the state of Ukraine apt for new bouleversements. In the circumstances of internal and external turbulence conclusion of a new social contract is crucial, at the same time the negative experience of generations which was not proper transformed, does not allow to address current social problems rationally and to consolidate society.Much is already said as for the role of memory in recreation of the past for the sake of the future, but the place of artistic practices in this process remains complex and uncomprehended. How do artistic practices objectivate social life and assist heeling? Visual art resonates with private or collective memory allowing new means of acceptation as well as perceptional rectification and conceptualization of experience associated with sorrow.This article suggests the theoretical and methodological analysis of the “work of sorrow” through the prism of artistic expressions, characterizes their influence of re-organization of traumatic memory and demonstrates the role of visual art as an instrument to operate with reminiscence.
Keywords: post-catastrophic memory, traumatic memory, visual arts, work of sorrow